Optimising data sharing whilst protecting participant privacy: a data note describing processed data from a qualitative study of healthcare professionals’ experiences of caring for women with false positive screening test results - Hannah A. Long; Peter Branney; David P. French; Joanna M. Brooks (Health Psychology and Behavioral Medicine)
Introduction The present article describes the processed data generated in a qualitative interview study and template analysis. Many women find the experience of being recalled and receiving a false-positive breast screening test result to be distressing. The interview study aimed to understand breast screening healthcare professionals’ (HCPs) experiences of providing care during the recall process and when receiving false-positive screening test results, including their communication with women around false-positive screening test results.Methods Twelve HCPs from a single screening unit in the English National Health Service Breast Screening Programme participated in semi-structured interviews in 2020. All participants were female. A range of HCPs roles were recruited, including advanced radiographer practitioners, breast radiographers, breast radiologists, clinical nurse specialists, and radiology healthcare assistants. The data were analysed thematically using template analysis from a limited realist perspective.Results A total of 20 data files are described, reflecting the iterative nature of template analysis. The files report various versions of codes, subthemes, themes, and every template produced during analysis. The files are publicly available on the Open Science Framework and UK Data Service (ReShare).Discussion This data note outlines our approach to conducting a template analysis of qualitative data while protecting highly identifiable data, which is stored in a non-public archive and only available to the study team. It offers a practical, worked example of the template analysis process, thereby providing a detailed illustration beyond the concise summaries typically found in published reports, and complementing methodological papers of template analysis.